Oscillating autonomy: a grounded theory study of women's experiences of COVID-19 infection during pregnancy, labour and birth, and the early postnatal period - Lili Peterson; Laura Bridle; Tisha Dasgupta; Abigail Easter; Stephanos Ghobrial; Irem Ishlek; Laura A. Magee; Amanda Mansfield; Ismini Panayotidis; Hannah Rosen O'Sullivan; Panicos Shangaris; Anita Banerjee; et al. (BMC, 2024)
Abstract Background Testing positive for COVID-19 was associated with higher rates of detrimental psycho-social and physical health outcomes. The COVID-19 pandemic caused unprecedented disruption to everyday life. This included major reconfiguration of maternal, child, and perinatal mental health and care services and provision. This study aimed to investigate the experiences of those who tested positive for COVID-19 during pregnancy, labour and birth, or the early postnatal period. Methods National on-line recruitment from across the United Kingdom resulted in sixteen mothers being invited to qualitative semi-structured interviews to understand the experiences of mothers who had been infected by COVID-19 during pregnancy, labour and birth, or the early postnatal period. Interviews were conducted, recorded, and transcribed using video-conferencing software. A Grounded Theory approach was used to analyse the data gathered pertaining to women's experiences of their positive COVID-19 diagnosis during pregnancy, labour and birth, or the early postnatal period. Results The theory of 'Oscillating Autonomy - Losing and Seeking to Regain Control by Striving for Agency' was developed, comprising three main themes: 'Anxious Anticipation: The fear of infection was worse than COVID-19 itself'; 'Fluctuating Agency: What changed when COVID-19 took control'; and 'Reclaiming Control: Seeking reassurance during COVID-19 positivity'. Testing positive for COVID-19 whilst pregnant, during labour or birth, or in the early postnatal period was associated with a perceived loss of control. Those who were able to regain that control felt more secure in their situation. Conclusions Support was paramount to manage increased vulnerability, as was reassurance achieved by information seeking and positive action including increased health monitoring and COVID-19 vaccination.